Trends in Research on Acute Kidney Injury: A Bibliometric Analysis of Academic Journals Published Between the Years 2000 and 2022 (Iranian Journal of Kidney Diseases, 2024)
Acute kidney injury (AKI) is a significant global health concern that was first recognized in 2004 and has subsequently affected more than thirteen million individuals each year, resulting in 1.7 million deaths. The present study explored the evolving of the research on AKI worldwide, specifically addressing the analysis of the  trends between the years 2000 and 2022 using the Web of Science Core Collection (WOSCC). CiteSpace software was employed to analyze 19,741 literature sources, which revealed shifts in keyword dynamics from foundational disease research to treatment prognosis and humanistic care.The keyword outbreaks occurred in the years 2004, 2010, and 2019 (i.e., significant occurrences or peaks related  to the specified keyword were observed in the years 2004, 2010, and 2019). The present study highlighted the transition of AKI studies from the initial concerns regarding definitions to further comprehensive inquiries regarding biomarkers, etiology, inductors, prediction, and prognosis. The future research focus could include  the Corona Virus Disease 2019 (COVID-19), machine learning, and continuous renal replacement treatment within the AKI realm.DOI: 10.52547/ijkd.8018